Regulation of Eosinophil Migration and Th2 Cell Function by IL-5 and Eotaxin - Mattes, J.; Foster, P.S. (Current Drug Targets - Inflammation & Allergy, 2003)
Asthma is characterized by elevated production of IgE, Th2 cytokines, chemokines, mucus hypersecretion, globlet cell metaplasia / hyperplasia, airway obstruction, eosinophilia and enhanced bronchial hyperresponsiveness. These hallmark features of asthma have all been linked to the effector functions of Th2 cytokines (e.g., interleukin-(IL)-4,5,9,10, and 13) in clinical and experimental investigations. This article will detail some of the pathogenic effects regulated by IL- 13, IL-5 and the eotaxin subfamily of chemokines to regulate certain aspects of allergic disease. In particular, the potency of IL-13 in inducing enhanced bronchial responsiveness to spasmogenic stimuli and mucus hypersecretion suggests a key role of this molecule in the induction of airways obstruction. Recent studies also indicate that IL-5 and eotaxin, through eosinophils, may regulate Th2 cell function and IL-13 production from this lymphocyte. Therefore, IL-5 and IL-13 signaling systems are not necessarily mutually exclusive effector mechanisms, but may also be integrated through eosinophils to regulate certain aspects of allergic diseases. Blocking IL-13, or pathways that may promote IL-13-associated allergic lung responses (IL-5 and eotaxin) could provide an important strategy to improve the specificity of asthma therapy.
Keywords: th2 cell function